Connecting Librarians and Faculty to Enhance Student Research Through Visual Mapping and Dialogue - Laverty, Corinne; Lee, Elizabeth A (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2016)
Five graduate students in education were videotaped while drawing a visual representation of and verbally describing their thesis topic. Dialogue among the faculty supervisor, librarian, and student followed and the map was further developed. Comparison between individual and collaborative maps revealed how faculty-librarian prompts extended and enriched students’ conceptualization of the research process and its underlying themes. Cinq étudiants des cycles supérieurs en Éducation ont été filmés en train de dessiner une représentation visuelle de leur sujet de thèse tout en le décrivant verbalement. Suite à un dialogue entre le directeur de thèse, le bibliothécaire et l'étudiant, le plan mis au point a été encore développé. Une comparaison entre les plans individuels et les plans mis au point collectivement a révélé combien les suggestions du professeur et du bibliothécaire ont permis d’étendre et d’enrichir les conceptualisations par les étudiants de leurs processus de recherche et des thèmes sous-jacents.